Another World? East Africa, Decolonisation, and the Global History of the Mid-Twentieth Century. (November 2021) - Milford, Ismay; McCann, Gerard; Hunter, Emma; Branch, Daniel
Abstract: This article proposes that there is a gap in our current understanding of the globalising and deglobalising dynamics of mid-twentieth-century East Africa, one that might be addressed by consolidating and taking forward recent developments in the historiography of decolonisation. Recent work by international historians has recovered the connected world of the 1940s to 1960s: the era of new postcolonial states, the 'Bandung moment', pan-African cooperation, and the early Cold War. Yet East Africa is less prominent in these histories than we might expect, despite the vibrancy of current work on this period in Kenya, Uganda, and Tanzania. Bringing these two fields into dialogue, through an explicitly regional East African framework and with a particular focus on individual lives, expands our understanding not only of the 'globalisation of decolonisation' but also of the deglobalising dynamics of the following decades that are frequently reduced to a history of global economic crisis.